Cộng đồng chia sẻ tri thức Doc24.vn

Bài 2 (Sách bài tập - trang 5)

Lý thuyết

Câu hỏi

Rút gọn các biểu thức sau :

a) \(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)

b) \(3x\left(c-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)

c) \(\dfrac{1}{2}x^2\left(6x-3\right)-x\left(x^2+\dfrac{1}{2}\right)+\dfrac{1}{2}\left(x+4\right)\)

Hướng dẫn giải

a)\(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)

=\(2x^3-3x-5x^3-x^2+x^2=-3x^3-3x\)

b) \(3x\left(x-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)

\(=3x^2-6x-5x+5x^2-8x^2+24=-11x+24\)

c) \(\dfrac{1}{2}x^2\left(6x-3\right)-x\left(x^2+\dfrac{1}{2}\right)+\dfrac{1}{2}\left(x+4\right)\)

\(=3x^3-\dfrac{3}{2}x^2-x^3-\dfrac{1}{2}x+\dfrac{1}{2}x+2=2x^3-\dfrac{3}{2}x^2+2\)

Các câu hỏi cùng bài học